1954
DOI: 10.1002/j.2050-0416.1954.tb06240.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of British Top Fermentation Yeasts: I. Introduction

Abstract: Methods employed in the isolation and storage of yeast clones are discussed. 10% wort‐gelatin is preferred as medium for development of giant colonies; at 18° C. good colony growth requires ca. 3 weeks. Owing to wort variations, initial comparisons should be made using the same wort. The incorporation in the medium of 0·1% of diphenyl as fungistatic has no adverse effect on the yeast. Growth records are made photographically and by verbal description.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1954
1954
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Thus, differentiation on the basis of flocculation characteristics (Gilliland, 1951;Hough, 1957) and assessment of fermentation performance and patterns of flavour volatile formation on a laboratory scale (Walkey and Kirsop, 1%9;Thorne, 1975) are still in widespread use. Similarly, conventional methods of microbial differentiation such as colonial morphology (Hall, 1954;Richards, 1%7) and patterns of carbon assimilation (Lodder and Kreger-van Rij, 1%7) are routinely applied to identification.…”
Section: Yeast Differentiationmentioning
confidence: 99%
“…Thus, differentiation on the basis of flocculation characteristics (Gilliland, 1951;Hough, 1957) and assessment of fermentation performance and patterns of flavour volatile formation on a laboratory scale (Walkey and Kirsop, 1%9;Thorne, 1975) are still in widespread use. Similarly, conventional methods of microbial differentiation such as colonial morphology (Hall, 1954;Richards, 1%7) and patterns of carbon assimilation (Lodder and Kreger-van Rij, 1%7) are routinely applied to identification.…”
Section: Yeast Differentiationmentioning
confidence: 99%
“…The techni ques employed for the isolation of the yeast clones and for the examination of their giant colony characteristics have been described in a preceding paper. 1 The initial experiments indicated that brewery pressed yeast contained a high proportion of dead cells (Table I). Tests were therefore carried out to investigate: (a) the effect of transportation and storage on yeast viability; and (6) the viability of a brewery yeast sampled during fermentation.…”
Section: Introductionmentioning
confidence: 99%